Tourists' dual-processing accounts of reasoning, judgment, and actions - Martin, D.; Woodside, Arch (Emerald Group Publishing Ltd., 2011)
Purpose – The purpose of this paper is to describe theory building and testing of dual processing of tourist reasoning, judgment, and actions. Design/methodology/approach – The paper applies micro-tipping point theory and qualitative comparative analysis, using case study data. Findings – Maps of the reasoning, judgments, and actions of five parties of tourist buying major services support dual-processing theory of deciding on destination choices. Research limitations/implications – This report does not include the attempt to generalize the findings to large survey samples of informants. Practical implications – Executives need to go beyond recognizing that what tourists report consciously may differ substantially from what they think unconsciously and to plan on collecting data on both dual processing modes of thinking. Originality/value – This paper breaks new ground in applying dual-processing theory in tourist behavior of buying major tourist services.